Arts-Based Interventions and Social Change in Europe - Kárpáti, Andrea (Routledge Advances in Art and Visual Studies, 2024)
This book presents 23 successful arts-based efforts to respond to social problems experienced by disadvantaged communities. The arts are a powerful means of fighting discrimination, marginalisation, neglect and even poverty. The educational programmes described in these chapters help stakeholders find solutions which are research-based, adaptable, repeatable and sustainable. Social problems that are addressed in this book include children living with physical challenges; suffering from financial and educational poverty; elderly women suffering from solitude; migrants facing a strange and not always welcoming cultural context; Roma youth fighting negative stereotypes and many more. Revealing the interconnectedness between social, economic and cultural exclusion, contributors planned interventions to develop skills, strengthen identities and build communities. This book will be of interest to scholars working in the visual arts, art education, design education, drama and theatre education and museum pedagogy. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.